Syair Aqaid Saeket sebagai Media Dakwah Kultural Kiai As’ad Syamsul Arifin - Ilyas Fahmi Ilyas; Rima Yulianti Dewi Lestari (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2022)
Kiai As'ad Syamsul Arifin is one of the scholars of the archipelago who is particularly well known for his struggles and great ideas. He is a descendant of Madurese who was born in Mecca and lives in Situbondo. During his lifetime, he has a part in struggle for independence of Indonesia, the establishment of Nahdlatul Ulama and return to the Khittah 26, especially the religious dynamics of the people of Situbondo and surrounding areas. In Situbondo, he has influenced people’s live in the religious, economic, education and socio-politics fields through the dakwah in behavior, speech and writings which are almost entirely written in Madurese language. By using qualitative methods, this study examines Kiai As'ad Syamsul Arifin's dakwah method through Aqaid Saeket poetry as his work in facilitating the process of delivering Islamic values. This study needs to be done as a reference to find out how the tactical steps taken by previous scholars in preaching culturally as well as transforming their knowledge to the community.[Kiai As’ad Syamsul Arifin merupakan salah satu ulama Nusantara yang terkenal dengan perjuangan dan ide-ide besarnya. Beliau keturuanan orang Madura yang lahir di Makkah dan hidup di Situbondo. Selama masa hidupnya, beliau banyak memberikan warna bagi kemerdekaan Indonesia, Berdirinya Nahdlatul Ulama dan kembalinya kepada Khittah 26, terlebih dinamika keagamaan masyarakat Situbondo dan sekitarnya. Di Situbondo, beliau telah mempengaruhi kehidupan masyarakatnya mulai dari keagamaan, perekonomian, pendidikan dan sosial politik melalui perjuangan dakwah berupa perilaku, ucapan maupun karya tulisnya yang hampir secara keseluruhan berbahasa Madura. Dengan menggunakan metode kualitatif, penelitian ini mengkaji metode dakwah Kiai As’ad Syamsul Arifin melalui syair Aqaid Saeket sebagai karyanya dalam mempermudah proses penyampaian nilai Islam. Hal ini perlu dilakukan sebagai referensi untuk mengetahui bagaimana langkah taktis yang dilakukan ulama terdahulu dalam berdakwah secara kultural sekaligus mentransformasikan keilmuanya kepada masyarakat.].